ANALISIS PENGARUH FAKTOR MAKROEKONOMI TERHADAP KINERJA REKSA DANA TERPROTEKSI DALAM MASA PANDEMI COVID-19 - Amadeus Sanda Layuk; Noer Azam Achsani; Bayu Bandono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Investment and the capital market are inseparable and have a strong influence on the economy both individually, in the business world, and nationally. One of the types of mutual funds in Indonesia that is in great demand by investors is Capital Protected Funds. This study aims to know the performance of Capital Protected Funds compared to market and other mutual funds in the 2016-2021 period. Then to analyze the influence of macroeconomic factors on the performance of Capital Protected Funds before and during the COVID-19 pandemic. The analysis used to process the data in this study was quantitative analysis using descriptive and multiple linear regression analysis. The result of this study is the performance of Capital Protected Fund in the period before the COVID-19 pandemic with Sharpe value of 0.669 was better for market performance and for money market and equity fund. However, during the COVID-19 pandemic the performance of Capital Protected Fund was decreased. Macroeconomic factors that showed a significant influence on the performance of Capital Protected Fund during the COVID-19 pandemic are the IHSG, Bank Indonesia interest rates, and the money supply.